Association between vitamin D receptor gene FokI polymorphism and skeletal fluorosis of the brick-tea type fluorosis: a cross sectional, case control study. Issue 11 (10th November 2016) - Yang, Dan; Liu, Yang; Chu, Yanru; Yang, Qing; Jiang, Wei; Chen, Fuxun; Li, Dandan; Qin, Ming; Sun, Dianjun; Yang, Yanmei; Gao, Yanhui
Abstract : Background: Brick-tea type fluorosis is a public health concern in the north west area of China. The vitamin D receptor (VDR)-FokI polymorphism is considered to be a regulator of bone metabolism and calcium resorption. However, the association of VDR-FokI polymorphism with the risk of brick-tea type fluorosis has not been reported. Materials and methods: A cross sectional, case control study was conducted in three provinces (Inner Mongolia, Qinghai and Sinkiang) in China. The fluoride content of Brick-tea water and urine was tested using the standards GB 1996–2005 and WS/T89-2006 (China), respectively. Skeletal fluorosis was diagnosed using the standard WS/192-2008 (China). The VDR-FokI polymorphism was detected by the Sequenom MassARRAY system. Result: Compared with carriers of the CC genotype, participants with the CT/TT genotype had a significantly decreased risk of skeletal fluorosis (OR=0.761 (95% CI 0.580 to 0.997)), after adjustment for risk factors. When investigated among ethnic groups, the protective effect of the CT/TT genotype was limited in the Mongolian participants (OR=0.525 (95% CI 0.278 to 0.991)). Moreover, the interaction of VDR-FokI with risk factors was only found in Mongolian participants: the protective effect of the CT/TT genotype was limited to participants with >7.0 mg/day daily intake of tea fluoride (OR=0.085 (95% CI 0.009 to 0.851), participants with >3.2 mg/L urine fluoride (OR=0.103 (95% CI 0.017 to 0.633)) or participants aged 46–65 years (OR=0.404 (95% CI 0.177 to 0.922). Conclusions: Our data suggest that the CT/TT genotype of VDR-FokI may be a protective factor for brick-tea type skeletal fluorosis, and this effect is pronounced in Mongolian participants.